Ex-vivo studies on friction behaviour of ureteral stent coated with Ag clusters incorporated in a:C matrix - Carvalho, Isabel (2018)
Coated ureteral stents must be placed in the human body without hurting the body tissue and, simultaneously, support the application without degrading the top active layer. In this work Ag clusters incorporated in a:C (Ag/ a:C) matrix were produced by plasma gas condensation process. After optimizing some deposition parameters, as cluster source pressure and power density, two different clusters sizes were obtained 11 ± 2 nm using cluster source pressure of 100 Pa, and a bimodal size using cluster source pressure of 200 Pa (31 ± 22 nm and 260 ± 135 nm). Ag/a:C coatings showed a total adhesion to substrate, without delamination of the film, even after a month of immersion in distilled water. The friction coefficient of the coatings and the uncoated reference were determined and show a reduction from 0.22 for the reference stent to 0.12 for the Ag/a:C coated stents produced at 100 Pa and to 0.16 for the Ag/a:C coated stents produced at 200 Pa.